Papillon-Lefevre syndrome: report of six patients and identification of a novel mutation - (:unkn) unknown (WILEY-BLACKWELL, 2016)
Papillon-Lefevre syndrome is an autosomal recessive genodermatosis typically manifesting with the constellation of palmoplantar keratoderma and progressive early-onset periodontitis. The cutaneous phenotype can be strikingly psoriasiform, possibly posing a diagnostic challenge. This rare disorder is caused by loss-of-function mutations in the CTSC gene, which encodes cathepsin C. We report six patients with Papillon-Lefevre syndrome from five consanguineous Turkish families, in whom genetic analysis of the CTSC gene revealed four recurrent mutations (c.415G>A; c.1015C>T; c.1019A>G; and c.103-105delCTG) and a novel missense mutation (c.117G>T) in the homozygous state.
Keywords: CATHEPSIN-C GENE; PREPUBERTAL PERIODONTITIS; FOLLOW-UP; ACITRETIN; KERATOSIS; DISEASE